Isolated night cough in children: how does it differ from wheeze?. Issue 4 (13th October 2020) - Jurca, Maja; Goutaki, Myrofora; Latzin, Philipp; Gaillard, Erol A.; Spycher, Ben D.; Kuehni, Claudia E.
It has been postulated that some children with recurrent cough but no wheeze have a mild form of asthma (cough variant asthma), with similar risk factors and an increased risk of future wheeze. This longitudinal study compared risk factors for isolated night cough and for wheeze in the Leicester Respiratory Cohort in children aged 1, 4, 6 and 9 years and compared prognosis of children with isolated night cough, children with wheeze and asymptomatic children. We included 4101 children aged 1 year, 2854 aged 4 years, 2369 aged 6 years and 1688 aged 9 years. The prevalence of isolated night cough was 10% at age 1 year and 18% in older children. Prevalence of wheeze decreased from 35% at 1 year to 13% at 9 years. Although several risk factors were similar for cough and wheeze, day care, reflux and family history of bronchitis were more strongly associated with cough, and male sex and family history of asthma with wheeze. Over one-third of preschool children with cough continued to cough at school age, but their risk of developing wheeze was similar to that of children who were asymptomatic at earlier surveys. Wheeze tracked more strongly throughout childhood than cough. In conclusion, our study showed that only some risk factors for cough and wheeze were shared but many were not, and there was little evidence for an increased risk of future wheeze in children with isolated night cough. This provides little support for the hypothesis that recurrent cough without wheeze may indicate a variant form of asthma. Children with isolated night cough do not have an increased risk of future wheeze, and risk factors for cough and wheeze only partially overlap. https://bit.ly/31IbXSC